PEMETAAN SENTRA PRODUKSI SAYURAN MENURUT WILAYAH DAN WAKTU DI KUPANG - Micha S. Ratu Rihi; Chris N. Namah; Melgiana S. Medah (Politeknik Pertanian Negeri Kupang, 2008)
Mapping The Center Vegetables Production By Area and TimeÂ In Region Of Kupang And Kupang City. The research aimed to identify the central production of several vegetables by the largest of harvesting, the greatest of production, and the continuity of production during one year in Region of Kupang and Kupang City. The reserch was conducted from March â€“ October 2007 with using method survey. All the sub region in Region of Kupang and Kupang City were determined as location of research.The result showed there were 17 kinds of vegetables planted and harvested in Region of Kupang and Kupang City and only two kinds of vegetables have central production. Those vegetables are spinach in sub Region Oebobo in Kupang City and swamp cabbage in sub region Kupang Timur in Region of Kupang. The other vegetables have no central production because the time of harvesting is uncontinue during a year. Furthermore, the time of harvesting is not continue because the lack of water for irrigation.Key words : Mapping, center vegetable production, area and time.